(untitled) - Lupica, Mike (New York, 2018)
"Robert B. Parker's iconic and irresistible PI Sunny Randall is back, and the stakes are higher than ever as she races to protect her ex-husband--and his Mafia family--from the vengeful plan of a mysterious rival. Sunny Randall is "on" again with Richie, the ex-husband she never stopped loving and never seemed to be able to let go, despite her discomfort with his Mafia connections. When Richie is shot and nearly killed, Sunny is dragged into the thick of his family's business as she searches for answers and tries to stave off a mob war. But as the bullets start flying in Boston's mean streets, Sunny finds herself targeted by the deranged mastermind of the plot against the Burke family, whose motive may be far more personal than she could have anticipated.."--
Kirkus Reviews
Booklist Starred Reviews
Publishers Weekly
Booklist
Adult
Keywords: Women private investigators; Fiction; Massachusetts; Divorced people; Fiction; Mystery fiction